2019
DOI: 10.1103/physrevlett.122.056601
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Axial-Torsional Anomaly in Weyl Semimetals

Abstract: We show that Weyl semimetals exhibit a mixed axial-torsional anomaly in the presence of axial torsion, a concept exclusive of these materials with no known natural fundamental interpretation in terms of the geometry of spacetime. This anomaly implies a nonconservation of the axial currentthe difference in current of left-and right-handed chiral fermions-when the torsion of the spacetime in which the Weyl fermions move couples with opposite sign to different chiralities. The anomaly is activated by driving tran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 86 publications
(110 reference statements)
2
59
0
Order By: Relevance
“…We note that the early papers [10][11][12] and [5,49] treat the anomaly in terms of an axial gauge field ∼ ±p Fl and the tetrad e a µ , leading to the requirement Λ = 0 in saturating the anomaly [81], in contrast to [67,68]. This is distinct from the emergent spacetime (14) or considerations of other systems, where such fields contribute only to a single anomaly [69,70,72].…”
Section: Pacs Numbersmentioning
confidence: 98%
See 1 more Smart Citation
“…We note that the early papers [10][11][12] and [5,49] treat the anomaly in terms of an axial gauge field ∼ ±p Fl and the tetrad e a µ , leading to the requirement Λ = 0 in saturating the anomaly [81], in contrast to [67,68]. This is distinct from the emergent spacetime (14) or considerations of other systems, where such fields contribute only to a single anomaly [69,70,72].…”
Section: Pacs Numbersmentioning
confidence: 98%
“…66. Related recent work discusses emergent tetrads, gauge fields and anomaly terms in Weyl SFs [67,68] and semimetals [69][70][71][72][73][74], without the framework of emergent conservation laws and geometry.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…They can emerge from dislocations [2][3][4][5], temperature gradient [6][7][8][9] and background rotation. Especially, in the Dirac and Weyl semimetals, due to their gapless spectrum and strong spin-orbit coupling [10,11], torsion has led to rich physical phenomena, for example, chiral zero modes trapped in dislocations [12,13], the chiral torsional magnetic effect [14] and other viscoelastic responses [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…(4) has far-reaching physical consequences. Here we focus on the torsion-induced effects which have attracted significant attention recently [3,[5][6][7][8][24][25][26][27][28][29][30][31][32][33][34]. It has been shown that the torsion gives a contribution to the chiral anomaly [2] through the Nieh-Yan term [35], which in the absence of spin connection reads…”
Section: Introduction-mentioning
confidence: 99%